ANALISIS PENGENDALIAN KUALITAS PRODUK BARREL MENGGUNAKAN METODE KAIZEN DAN PDCA FRAMEWORK DI PT. XYZ - Pranata, Dean; Windyatri, Hasyrani; Suhendra, Suhendra (LPPM Universitas Pahlawan Tuanku Tambusai, 2024)
PT. XYZ is a medical device manufacturing company that produces components for syringes, one of which is the Barrel product. The Barrel product has high demand, so effective quality control is essential to reduce the defect rate. This study aims to analyze ways to reduce defects in the Barrel product using the Kaizen and Plan-Do-Check-Action (PDCA) methods. In the planning phase (Plan), the dominant types of defects were identified using a Pareto diagram, which revealed three main defect types, with shortmold as the primary focus. The causes of this defect were analyzed using a Fishbone diagram. In the Do phase, corrective actions were implemented by setting objectives and goals for improvement, as well as identifying defective products with the help of the 5W+1H tool. The Check phase involved further inspection using a Check Sheet to analyze data showing a reduction in defects between October 2023 and January 2024. In the Action phase, quality control was implemented by monitoring employee performance and product quality, as well as evaluating the results of the improvements. The results of the study indicate a significant reduction in the number of defective products following the implementation of corrective actions.